Prevalence of Major Intestinal Nematodes of Equines in Jimma Town, South Western Ethiopia - Bamlaku Andarge; Chaltu Muhammed; Gebawo Tibesso (International Journal of Veterinary Science and Research - Peertechz Publications, 2017)
A cross sectional study was conducted from October, 2015 up to March, 2016 in Jimma town, Oromia Regional State of South West Ethiopia, with the objective of determining the prevalence of intestinal nematode parasites of equines and the effect of putative risk factors on the rate of helminth parasite infections. A total of 400 Equines; donkeys (n=29), horses (n=317) and mules (n=54) were included in the study. Out of 400 faecal samples examined, three species of nematode eggs were identifi ed during the study period. Coprological examination conducted using fl otation technique revealed an overall point prevalence of 72.25%. The most common nematodes encountered in order of their predominance were, Strongyles (63.25%), Parascaris equorum (16.5%), Oxyuris equi (4.25%), and mixed infection was found to be (10.75%). The results of statistical analysis of different risk factors with risk of intestinal nematode infection indicates a signifi cant difference (P<0.05) between the species of equine and strongyle infection rate, body condition scores with Strongyle and Parascaris equorum infection rate. But species of the animal was not signifi cantly associated with Parascaris equorum (P<0.05). The infection rate of Oxyurisequi was not signifi cantly associated with body condition score, age and species of equines (P> 0.05 for all variables).Statistical analysis of the result also showed no signifi cant difference (p>0.05) in the prevalence of intestinal nematodes with sex of the animal, although it was relatively higher in male than female individuals. Therefore, the present study showed that intestinal nematodes are an important health problem in the area affecting the wellbeing and productivity of the equines.